Awake Surgery for Left Posterior Insular Low-Grade Glioma Through the Parietorolandic Operculum: The Need to Preserve the Functional Connectivity. A Case Series - Duffau, Hugues (Frontiers in Surgery, 2022)
Objective: Surgical approach to low-grade glioma (LGG) involving the posterior insula is challenging, especially in the left hemisphere, with a high risk of sensorimotor, language or visual deterioration. Here, a case series of 5 right-handed patients harboring a left posterior insular LGG is reported, by detailing a transcortico-subcortical approach. Method: The five surgeries were achieved in awake patients using cortical and axonal electrostimulation mapping. The glioma was removed through the left Rolandic and/or parietal opercula, with preservation of the subcortical connectivity. Results: The cortical mapping was positive in the 5 patients, enabling to select an optimal transcortical approach, via the antero-lateral supramarginal gyrus in 4 patients and/or via the lateral retrocentral gyrus in 3 cases (plus through the left superior temporal gyrus in one case). Moreover, the white matter tracts were identified in all cases, i.e. the lateral part of the superior longitudinal fasciculus (5 cases), the arcuate fasciculus (4 cases), the thalamocortical somatosensory pathways (4 cases), the motor pathway (1 case), the semantic pathway (3 cases), and the optic tract (1 case). Complete resection of the LGG was achieved in 2 patients and near-total resection in 3 patients. There were no postoperative permanent sensorimotor, language or visual deficits. Conclusion: A transcortical approach through the parieto-rolandic operculum in awake patient represents a safe and effective access to the left posterior insular LGG. Detection and preservation of the functional connectivity using direct electrostimulation of the white matter bundles is needed in this cross-road brain region to prevent otherwise predictable postsurgical impairments.